Competency Needs of Secondary School Teachers of Lopez West District based on PPST Domains - Velano , Abegail (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the competency needs of secondary school teachers in the Lopez West District, Division of Quezon, using the Philippine Professional Standards for Teachers (PPST) as the guiding professional standards framework and an input–process–output logic for translating results into a proposed Teacher Enhancement Program. The research employed descriptive-survey, descriptive-evaluative, and descriptive-comparative approaches across nine secondary schools. From a population of 304 teachers, 121 respondents were selected through stratified random sampling (Slovin’s formula, 7% margin of error). Data were gathered using a PPST-based checklist with a two-part format (demographic profile and seven PPST domains) rated on a 4-point competency scale; the instrument underwent expert validation. Analyses included percentages, weighted arithmetic means, tests of homogeneity and normality, and nonparametric group comparisons using Mann–Whitney U and Kruskal–Wallis H tests. Findings showed respondents were predominantly female and early-career, largely baccalaureate degree holders, and mostly married. Overall competency across all seven PPST domains was rated Competent, with relatively higher ratings in Diversity of Learners and Content Knowledge and Pedagogy, and comparatively lower ratings in Personal Growth and Professional Development, Community Linkages and Professional Engagement, and Learning Environment. No significant differences in competency needs were found by sex, while significant differences emerged when grouped by age, civil status, educational qualification, and length of service. Based on lower-rated indicators across domains, a Teacher Enhancement Program was developed to address prioritized competency needs through targeted professional learning and school-level support mechanisms. This study aligns with SDG 4 (Quality Education) and supports SDG 8 (Decent Work and Economic Growth) through standards-based teacher upskilling and strengthened professional practice. Its sustainability impact lies in promoting an institutionalized, evidence-informed professional development system that improves instructional quality, inclusive practice, and stakeholder engagement over time.